Qualidade de vida no trabalho : um estudo com os servidores do Instituto Federal do Espirito Santo - Avanci, Lílian Tonete Ambrozim (2018)
Quality of Work Life (QWL) is a term that possesses multidimensional variables, having subjectivity as main characteristic and being perceived in a singular way by each person. The purpose of this paper was to analyze quality of life at work according to the perception of public servants at Instituto Federal do Espirito Santo (Ifes), following Walton’s (1973) theoretical model. To that end, a descriptive research was conducted using a field survey, both qualitative and quantitative. Data collection happened in two phases, the first being a documental research, which aimed information about The Quality of Life at Work Program (QLWP) at Ifes. In the second, an open/closedquestion questionnaire was applied to the servants, with 446 participants. The analyses were quantitative, using descriptive statistics, exploratory factorial analyses and non-parametrical tests, Mann-Whitney and Kruskal-Wallis. For the qualitative approach, were used documental analyses, codification and categorization, according to Gibbs (2009). The results have shown that the QLWP at Ifes is incipient with predominant sporadic actions. The QWL’s evaluation scale, in a range from 1 to 5, was 3, 62 average, indicating satisfactory tendency. In the factorial analyses were extracted four factors which explain 67,96% of total variation, being the use of capacities , integration and constitutionalism the strongest one, with 3,88 average, while the weakest one was the Growing opportunities and social relevance factor, with 3,34. It was revealed that there are significant differences in perception of QWL, considering the variables: sex, career, work time at the institution and work place. It was identified as well that participants understand QWL as among other terms: respect, satisfaction, welfare, health and relationship. The results also show that aspects that bring satisfaction and dissatisfaction in relation to work are spread in different categories. The biggest satisfaction is in the Social relevance of work in life; on the other hand, Social integration in the organization is the biggest dissatisfaction. The product from this paper was a report with all main problems and deficiencies found and suggestions on how to implement solutions. Finally, this paper was developed according to the research line Operation management in the public sector.